Theoretical Regulation of Delimitation of Metal Level Decrease in the Furnace in Case of Pneumatic Dosing Device of Metal - Ružbarský, Juraj; Majerník, Rastislav (Manufacturing Technology Journal, 2017)
Article deals with the during operation of pneumatic dosing device designed for die casting machines where the metal level in the furnace decreases stepwise by which the period of dosing of the filling mould is prolonged. We also deal the regulation of delimitation of metal level decrease in the furnace based upon the pneumatic principle.
Keywords: Theoretical Regulation; Die casting; Air pressure; Dosing device